Modeling Long-Term Erythropoietic Recovery After Allogeneic Stem Cell Transplants in Pediatric Patients - von Asmuth, Erik G. J.; Mohseny, Alexander B.; Putter, Hein; Schilham, Marco W.; Lankester, Arjan C. (Frontiers in Pediatrics, 2020)
Long term erythropoietic reconstitution after allogeneic hematopoietic stem cell transplantation (alloHSCT) has not been extensively studied. We aimed to describe erythropoietic reconstitution as an indicator of long-term graft function by modelling haemoglobin levels during the first three years post HSCT in paediatric patients. We retrospectively included 414 patients and 11957 measurements. The largest haemoglobin increase was at day 45 and levels reached a steady state at day 648 with a level of 7.48 mmol/L. In patients transplanted for haematological malignancies haemoglobin levels normalized faster (p<0.0001). Increasing patient age correlated with faster recovery (p<0.0001), while donor age had no influence. Conditioning, donor type and graft source did not influence recovery significantly. In the ABO mismatched group there was a transient negative effect on haemoglobin levels, and a delay in reticulocyte recovery (21 vs 19 days; p=0.012). In contrast, haemoglobin levels reached a higher plateau beyond 9 months in these patients (p<0.0001). After alloHSCT, experiencing a CMV reactivation negatively affected reconstitution (p=0.034), while EBV reactivations and acute graft vs host disease did not. In summary, erythropoietic recovery was mainly influenced by patient factors and primary disease, and less influenced by donor factors.